SOSIALISASI PERAWATAN KENDARAAN SEPEDA MOTOR DI KAMPUNG MALAUMKARTA DISTRIK MAKBON - Dayera, Disabella; Toumahuw, Hengky; Nurul Kusumawardana, Ahmad Rizal; Aryanto, Ishak; Bastian, Christina (SOLIDEO Jurnal Pengabdian Masyarakat, 2023)
Motorcycle maintenance knowledge and abilities are crucial for vehicle owners to possess. The most common mode of ground transportation for everyday tasks among residents of Malaumkarta Village, Makbon District, and Sorong Regency is a motorbike. Due to the fact that a public or official workshop is located 48 km from the city core, issues relating to a lack of knowledge and expertise in car maintenance must be rectified. The PkM Team arranges socialisation, training, and service activities for motorcycle vehicles based on these issues to solve societal issues. Based on the results of the implementation of this service activity, it can be concluded as follows: The results of the recapitulation of the final grades of training participants at the time of evaluation by the resource team (lecturers) showed a significant increase compared to before the provision of material. It can be concluded that the trainees experienced an increase in knowledge, understanding, and skills in motorcycle maintenance and service after this service activity. As for the problem of damage to motorbikes owned by residents, it can be directly repaired by mechanics from the PkM Team.